Triplet BODIPY and AzaBODIPY Derived Donor‐acceptor Dyads: Competitive Electron Transfer versus Intersystem Crossing upon Photoexcitation. Issue 1 (10th September 2019) - Shao, Shuai; Gobeze, Habtom B.; Bandi, Venugopal; Funk, Christiane; Heine, Brian; Duffy, Maddie J.; Nesterov, Vladimir; Karr, Paul A.; D'Souza, Francis
Abstract: The bis‐iodo β‐pyrrole‐substituted BF2 ‐chelated dipyrromethene, I2 BODIPY, and its structural analogue BF2 ‐chelated aza dipyrromethene, I2 azaBODIPY, carrying a nitrogen at the meso ‐position instead of carbon, were synthesized and characterized as new set of triplet sensitizers using different techniques. These sensitizers were further functionalized with fullerene, C60, at the central boron atom to build donor‐acceptor conjugates. Using spectral, electrochemical, and computational methods, these conjugates were characterized, and the energy levels were established. Intersystem crossing to populate the triplet state was observed upon excitation of I2 BODIPY and I2 azaBODIPY, however, the measured rates of k ISC were found to be nearly two orders of magnitude higher for I2 azaBODIPY ( k ISC ∼10 11  s −1 ) compared to I2 BODIPY ( k ISC ∼10 9  s −1 ). The energetics, k ISC, and position of HOMO and LUMO levels was found to control the ability of the dyad to undergo electron transfer, although the donor‐acceptor distances were virtually the same in both I2 BODIPY‐C60 and I2 azaBODIPY‐C60 conjugates. Free‐energy calculations revealed that the photoinduced electron transfer process was thermodynamically feasible from only the singlet excited states in both conjugates. Consequently, electron transfer from the 1 I2 BODIPY* in competition with intersystem crossing was witnessed in the case of I2 BODIPY‐C60 dyad while in the case of I2 azaBODIPY‐C60 dyad, excitation of azaBODIPY led to a short‐lived charge transfer state involving the catechol bridge followed by populating the low‐lying 3 I2 azaBODIPY* state without promoting the process of charge separation involving C60 . The lifetime of the charge‐separated states was in the ns range in the I2 BODIPY‐C60 conjugate both in polar and nonpolar solvents. Abstract : Keep it moving ! Two donor‐acceptor conjugates, I2 BODIPY‐C60 and I2 azaBODIPY‐C60, derived from triplet sensitizers, were newly synthesized and characterized. Photoinduced charge separation in these dyads from different excited states (singlet vs. triplet) is systematically probed in polar and nonpolar solvents using ultrafast pump–probe techniques.